Block Inspection Policy Model with Imperfect Maintenance for Single-unit Systems. (2017) - Pietruczuk, Anna Jodejko; Werbińska-Wojciechowska, Sylwia
Abstract: In the presented paper, authors focus on development of mathematical delay-time model for single-unit technical systems with taking into account the assumption of imperfect inspection actions performance. Thus, the briefly literature review in the area of delay-time modelling for single-unit systems is provided. This gives the possibility to present the maintenance model for the case of one component system performing with imperfect inspection. Authors also discuss the sensitivity analysis of given analytical model. The directions for further research work are defined.